2019
DOI: 10.1080/1331677x.2019.1697332
|View full text |Cite
|
Sign up to set email alerts
|

The influence of family income on students’ family resilience in Croatia

Abstract: The study basically examines if there are differences in the factors of students' family resilience regarding the level of their families' income. Two additional hypotheses have also been tested, concerning influence of income level on students' expression of problems and difficulties to family members and on religiosity. The study has been done on a sample of students from the Faculty of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…In contrast, the family profile of cluster LR was as follows: Patients had the most severe stroke (Rankin score = 2.5 ± 1.3) and the lowest level of income; the education level of patients and caregivers were low; the proportion of living in Shangqiu (44.3%) and the unemployed rate of caregivers were the highest in three clusters. As a result, we deduced that factors, including the education level, family income and stroke severity of patients influence clustering, which is consistent with previous findings that family income could influence family resilience (Radetić‐Paić & Černe, 2020). Also, special attention should be paid to families with severe stroke patients, low income and poor education, during the hospitalisation of stroke patients.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, the family profile of cluster LR was as follows: Patients had the most severe stroke (Rankin score = 2.5 ± 1.3) and the lowest level of income; the education level of patients and caregivers were low; the proportion of living in Shangqiu (44.3%) and the unemployed rate of caregivers were the highest in three clusters. As a result, we deduced that factors, including the education level, family income and stroke severity of patients influence clustering, which is consistent with previous findings that family income could influence family resilience (Radetić‐Paić & Černe, 2020). Also, special attention should be paid to families with severe stroke patients, low income and poor education, during the hospitalisation of stroke patients.…”
Section: Discussionsupporting
confidence: 89%
“…Radeti-Pai and Erne (2020) discovered that highly resilient families exhibit open communication patterns. 24 This communication pattern includes an open environment for family members to express or share feelings and a condition that demonstrates a frank and productive open attitude in discussing family problems. 24 In the context of COVID-19, the importance of family processes in risk mitigation and resilience promotion through shared family beliefs and close relationships is provided.…”
Section: Original Articlementioning
confidence: 99%
“…24 This communication pattern includes an open environment for family members to express or share feelings and a condition that demonstrates a frank and productive open attitude in discussing family problems. 24 In the context of COVID-19, the importance of family processes in risk mitigation and resilience promotion through shared family beliefs and close relationships is provided. 25 Walsh (2002) suggests that belief systems are made up of a process of meaningmaking, transcendence or spirituality, and a positive outlook.…”
Section: Original Articlementioning
confidence: 99%
“…On the contrary, a low level of education cannot be interpreted as weak family resilience (52). Family resilience also cannot be influenced by family types ranging from nuclear families, extended families, and singles, these types of families do not guarantee family resilience, especially during the COVID-19 pandemic (36,53). Therefore, it can be concluded that age cannot determine whether a person's or family's mental, psychological, and social problems are affected by the COVID-19 pandemic.…”
Section: Religious Coping Closely Relates To Communication Including ...mentioning
confidence: 99%